Expert consensus for a digital peer-led approach to improving physical activity among individuals with spinal cord injury who use manual wheelchairs. (2nd January 2023) - Best, Krista L.; Bourassa, Sophie; Sweet, Shane N.; Routhier, François
Abstract : Context: Active Living Lifestyles for manual wheelchair users (ALLWheel) uses a digital peer-led approach to incorporate two behavior change theories to address a critical need for leisure-time physical activity (LTPA) programs for individuals with spinal cord injury (iSCI). Objective: The objective of this study was to obtain expert opinion and consensus for the ALLWheel program. Design: Mixed-methods (qualitative and quantitative) were used to gather expert opinion and consensus for the ALLWheel program using an action research approach. Setting: Rehabilitation center. Participants: Experts in SCI and LTPA included iSCI who used manual wheelchairs, healthcare professionals, and community collaborators. Procedures: Two, 90-minute focus groups were conducted and transcribed verbatim, analyzed thematically, and the results were used to create a Delphi survey. Delphi surveys were completed online using consecutive rounds until ≥70% consensus per item was attained. Cumulative percent concordances were calculated to determine consensus. Results: Twelve experts in SCI and LTPA participated in focus groups. Four themes were generated: Need for LTPA programs; Important considerations; Perceptions about peer-coaches; and Feelings about smartphones, which were used to generate the Delphi survey. Consensus on the ALLWheel program was attained in two rounds. Conclusions: Experts established a need for fun and personalized community-based LTPA programs. Ensuring that healthcare professionals would be involved in the ALLWheel program alleviated safety concerns, and experts agreed there were benefits of peers delivering the program. Experts agreed that the ALLWheel program targeted important psychological factors ( i.e. autonomy, relatedness, self-efficacy, and motivation) and affirmed the potential for a potentially large geographic reach.